2018
DOI: 10.4236/health.2018.104033
|View full text |Cite
|
Sign up to set email alerts
|

Household Environment and Malaria in Pregnancy in Ibadan, Nigeria

Abstract: Introduction: Malaria in pregnancy, which enormously creates substantial risks for the mother and her fetus, is a public health problem in Nigeria. Design and Methods: Through questionnaire administration, this cross-sectional survey investigates the influence of the household environment on malaria preventive and treatment behaviors among 300 pregnant women in two selected areas of Oyo State, Nigeria. In addition, four focus group discussions and four in-depth interviews were conducted, all between October 20… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
2
0

Year Published

2020
2020
2020
2020

Publication Types

Select...
2
1

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(2 citation statements)
references
References 24 publications
0
2
0
Order By: Relevance
“…In a study carried out in Ibadan, Nigeria, preventive behavior practiced by women was positively in uenced by their level of education [21]. There was a similar nding in another study which found that women who were exposed to educational programs on the adverse effects of malaria in pregnancy were more likely to use insecticide treated nets [22].…”
Section: Discussionmentioning
confidence: 76%
“…In a study carried out in Ibadan, Nigeria, preventive behavior practiced by women was positively in uenced by their level of education [21]. There was a similar nding in another study which found that women who were exposed to educational programs on the adverse effects of malaria in pregnancy were more likely to use insecticide treated nets [22].…”
Section: Discussionmentioning
confidence: 76%
“…In a study carried out in Ibadan, Nigeria, preventive behavior practiced by women was positively influenced by their level of education [ 21 ]. There was a similar finding in another study which found that women who were exposed to educational programs on the adverse effects of malaria in pregnancy were more likely to use insecticide treated nets [ 22 ].…”
Section: Discussionmentioning
confidence: 99%